Profile of Teenage Pregnancy in H. Adam Malik Hospital Medan in 2011-2015 - Sukatendel, Khairani; Iman Helmi Effendi; Sarah Dina; S. A. Nasution; Marpaung, Johny; I. Hamidi (Talenta Publisher, 2019)
Many of the teenagers who enter pregnancy would cause a decline in health and nutritional status. Delivery at an early age was associated with a greater health risk for the mother. To assess the profile of teenage pregnancy in H. Adam Malik Hospital Medan year 2011-2015. This study was conducted with descriptive study design using secondary data from medical records. There were 128 patients who became pregnant in their teens. Then the data were tabulated and presented in the form of frequency distribution table and were analyzed descriptively. Most pregnant women came to the hospital for parturition (60.1%) followed by preeclampsia / eclampsia (14.8%). The way of delivery of pregnant adolescent women was vaginal (52.3%) followed by cesarean (36.7%). There was no significant relationship between adolescent age of pregnant and newborn weight. There was no significant relationship between the age of the adolescent and method of delivery. Most teenage pregnancy occured between 17-19 years. Most pregnant teenagers delivered vaginally, and most of the newborns were normoweight